Living Hadits, Precedent Theory and Health Quarantine: Studies on Maslahah Mursalah, Sadd al-Dzariah and Ta'un in The Prophetic Tradition - Azis Arifin; JM Muslimin; Wildan Munawar (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2021)
As legal theories and instruments that have been legitimized by many scholars, Maslahah Mursalah and Sadd al-Dzariah become important analytical tools to be observed at the form of their use in the prophetic tradition. They have also a practical significance and relevance in the time of pandemic (Covid-19). Actually, Hadith of Ta’un can be positioned as a precedent value and practice for the Maslahah Mursalah and Sadd al-Dzariah theories in Islamic law. How the Prophet's advice that has been described in the hadith is related to keeping yourself from contracting the virus outbreak, it seems that it can be used as the basis for the current pandemic situation. This research is qualitative in nature, done by using the Usul Fiqh and Hadith Science approaches, emphasizing the use of legal precedent theories. The core existing data is a prophetic living tradition. It is presented in an analytical descriptive manner. The results of this study prove that the Hadith Ta’un is a practical precedent that can legitimize the theory of Maslahah Mursalah and Sadd al-Dzariah as a tool to explore Islamic law and cope with the current situation of the pandemic. The values and principles contained in this Hadith are still relevant today: they can be applied in preventing the transmission of the Covid-19, namely by physical distancing as well as health quarantine and several related adjustments.